Toward Dynamic Prescribing Information: Codevelopment of Companion Model‐Informed Precision Dosing Tools in Drug Development. Issue 4 (30th November 2018) - Polasek, Thomas M.; Rayner, Craig R.; Peck, Richard W.; Rowland, Andrew; Kimko, Holly; Rostami‐Hodjegan, Amin
Abstract: Model‐informed precision dosing (MIPD) is biosimulation in healthcare to predict the drug dose for a given patient based on their individual characteristics that is most likely to improve efficacy and/or lower toxicity compared with traditional dosing. Despite widespread use of biosimulation in drug development, MIPD has not been adopted beyond academic‐hospital centers. A reason for this is that MIPD requires more supporting evidence in the language that everyday doctors understand—evidence‐based medicine. In this commentary, codevelopment of companion MIPD tools during drug development is advocated as a way to accelerate the generation of the evidence required for broader clinical implementation of MIPD. Such tools have the potential to evolve into "dynamic" prescribing information that could guide dose selection for complex patients.